FORMULATION AND NUTRIENT ANALYSIS OF STEVIA (STEVIA REBAUDIANA) INCORPORATED VALUE ADDED PRODUCTS - Prabha, V. Krishna; M. A., Mahaboob (International Journal of Current Pharmaceutical Research, 2015)
Objectives: To incorporate the stevia in the value added products like jam, Ice cream and chocolates and conduct organoleptic evaluation of the stevia incorporated value added products and to analyse the nutrient contents of the stevia incorporated prepared items. To create awareness of the beneficial effects of the Stevia to the diabetic patients. Methods: This study we incorporated the stevia in many value added products like chocolate, ice cream, cake, jam and milk shake. The Organoleptic evaluation was conducted and the results were tabulated. The nutrients like energy, protein, fat, calcium, phosphorous, iron, carbohydrate, dietary fibre, Vitamin C were analyzed using standard methods. The Physico-chemical constituents like moisture, ash, acid insoluble ash, and total sugar were analyzed using standard methods. The mean and standard deviation was used for the statistical analysis. Results: The sensory evaluation of Stevia incorporated mixed fruit jam and chocolate got less marks when compared to the control sample. Stevia incorporated chocolate cake got maximum marks when compared to the control sample. The energy and the carbohydrate was very low for the stevia incorporated mixed fruit jam, Chocolate Cake, Chocolate and Chocolate Ice Cream when compared to the control sample. Protein and fat of Stevia incorporated mixed fruit jam. Chocolate Cake, Chocolate and Chocolate Ice Cream have maximum value when compared to the control. Conclusion: It is very useful to prepare many sweets for the diabetic patients with the incorporation of stevia. The supplementation and evaluation of blood glucose levels for diabetic patients will be used to generate new views in future research. So as a nutritionist, we have to create the awareness about the benefits of Stevia to the community.